Validation of the modified Telephone Interview for Cognitive Status in amnestic Mild Cognitive Impairment and intact elders - Duff, Kevin (2009)
Although the modified Telephone Interview for Cognitive Status (mTICS) is frequently used as a screening measure of cognition in dementia and aging studies, it has not been validated in individuals with milder cognitive impairments. The current study compared two groups (amnestic Mild Cognitive Impairment [n=61] and cognitively intact elders [n=62]) on the mTICS and used regression models to predict baseline scores on standardized memory tests using baseline mTICS scores. Baseline mTICS scores were also used to predict one-year follow-up scores on memory tests in a subsample (n=91). Large group differences (p<0.01) were found between the amnestic individuals and their healthy peers on the mTICS total score, two factor scores, and 3 of 14 individual items. Baseline mTICS scores predicted between 22 – 43% of baseline memory composite scores and 21 – 28% of one-year memory composite scores. Overall, these results provide additional validation of the mTICS as a valuable screening instrument for cognition in individuals with milder cognitive impairments.